Ipsilateral masking between acoustic and electric stimulations - Lin, Payton (Acoustical Society of America, 2011)
Residual acoustic hearing can be preserved in the same ear following cochlear implantation with minimally traumatic surgical techniques and short-electrode arrays. The combined electric-acoustic stimulation significantly improves cochlear implant performance, particularly speech recognition in noise. The present study measures simultaneous masking by electric pulses on acoustic pure tones, or vice versa, to investigate electric-acoustic interactions and their underlying psychophysical mechanisms. Six subjects, with acoustic hearing preserved at low frequencies in their implanted ear, participated in the study. One subject had a fully inserted 24 mm Nucleus Freedom array and five subjects had Iowa∕Nucleus hybrid implants that were only 10 mm in length. Electric masking data of the long-electrode subject showed that stimulation from the most apical electrodes produced threshold elevations over 10 dB for 500, 625, and 750 Hz probe tones, but no elevation for 125 and 250 Hz tones. On the contrary, electric stimulation did not produce any electric masking in the short-electrode subjects. In the acoustic masking experiment, 125–750 Hz pure tones were used to acoustically mask electric stimulation. The acoustic masking results showed that, independent of pure tone frequency, both long- and short-electrode subjects showed threshold elevations at apical and basal electrodes. The present results can be interpreted in terms of underlying physiological mechanisms related to either place-dependent peripheral masking or place-independent central masking.